Decision Making Style of Senior Secondary School Principals Related to Emotional Intelligence with Reference to Their Gender: The Influence of Gender on the Decision Making Style and Emotional Intelligence of Senior Secondary School Principals (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main purpose of the study was to study the relation of decision making style of secondary school principals with reference to their gender. The sample of two hundred (76) headmasters was drawn through stratified random sampling technique from different secondary schools of six Blocks of the Kumaon region of Uttarakhand. Decision making style scale developed by Ganihar (2005) and the Teacher’s Emotional Intelligence Inventory (TEII-) (Mangal, Shubhra, 2005) was administrated to collect data from sample subjects. Analysis of collected data were done with the help of correlation calculated using software SPSS. The results of the study revealed that routine, compromise and heuristic decision making styles of male principals is not correlated with total emotional intelligence. On the other hand total emotional intelligence of female Principals is correlated with routine, compromise, and heuristic decision making styles. From the results obtained from the present study it can be concluded that female principal use their emotional intelligence in their decision making styles more than male principals.